Designing some supplementary speaking activities to the course book “Lifelines Elementary” for the 1st year students at Vietnam Vocational College of Technique – Craft Art = Thiết kế một số hoạt động nói bổ sung cho giáo trình “Lifelines Elementary” cho s - Đoàn, Thị Lê (University of Languages and International Studies, 2017)
47 p. + CD-ROM